Problems and solutions in zakat digitalization: Evidence from South Kalimantan, Indonesia - Sri Maulida; Fahmi Al Amruzi; Budi Rahmat Hakim; Irfan Syauqi Beik (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – This study aims (i) to analyze the readiness of zakat management institutions in zakat digitalization and (ii) to analyze the problems and solutions in managing zakat funds through digital platforms.Methodology – The study used two methods, called the interview and the Delphi-ANP methods. The data used in this study were the results of interviews with zakat managers (OPZ) in South Kalimantan (BAZNAS and LAZNAS). Besides practitioners, it also involved experts from various universities in South Kalimantan.Findings – The results showed that most zakat institutions in South Kalimantan, Most zakat institutions have a good understanding and readiness to shift to digital platforms. Based on the analysis of problems and solutions in using digital platforms in zakat management, the study found alternative priority problems and solutions for zakat institutions. The problems and solutions covered human resources, IT, institution management and socialization and communication, muzakki, society, government and digitization. In particular, the main cluster of priority problems was management, and the main cluster of priority solutions included human resources.Originality – The researchers reviewed several studies that explained problems and theories of zakat management through digital platforms. However, there is still seemingly no study reviewing problems to manage zakat funds through digital platforms provided by zakat institutions.Practical implications – This research shows that OPZ needs to recruit IT and Digital Marketing people. In addition, it suggests OPZ designs and creates crowdfunding, e-wallet, e-commerce, website, and social media. Following that, OPZ should do digital planning for zakat collection and training conducted by BAZNAS Province and Center to OPZ periodically. They also need to establish a partnership with scholars (Ulama) and the government agencies to increase the payment zakat digitally.